2010
DOI: 10.3390/ma3010216
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SO2 Dry Deposition on Porous Dolomitic Limestones

Abstract: The present study is concerned with the assessment of the relative resistance of a monumental dolomitic limestone (Laspra – Spain) used as building material in stone monuments and submitted to artificial ageing by SO2 dry deposition in the presence of humidity. To investigate the protection efficiency of different polymeric coatings, three commercially available siloxane-based oligomers (Lotexan-N, Silres BS 290 and Tegosivin HL 100) and a newly synthesized hybrid nanocomposite with silsesquioxane units (TMSPM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…7 The aim of this study was the evaluation of a newly synthesized silsesquioxane-based nanocomposite material in comparison to three widely used siloxane-based polymers against SO 2 action on a monumental limestone, Repedea, traditionally used as a building stone in the north-eastern part of Romania. A previous article 8 showed that the silsesquioxane-based nanocomposite material provided better protection against SO 2 dry deposition when applied on a monumental dolomitic limestone (Laspra from Spain) used in many stone monuments in the northern part of Spain called Asturias. Silsesquioxane-based hybrid nanocomposites were recently tested as strengtheners 9 and/or water repellents 10 in stone conservation.…”
Section: Introductionmentioning
confidence: 99%
“…7 The aim of this study was the evaluation of a newly synthesized silsesquioxane-based nanocomposite material in comparison to three widely used siloxane-based polymers against SO 2 action on a monumental limestone, Repedea, traditionally used as a building stone in the north-eastern part of Romania. A previous article 8 showed that the silsesquioxane-based nanocomposite material provided better protection against SO 2 dry deposition when applied on a monumental dolomitic limestone (Laspra from Spain) used in many stone monuments in the northern part of Spain called Asturias. Silsesquioxane-based hybrid nanocomposites were recently tested as strengtheners 9 and/or water repellents 10 in stone conservation.…”
Section: Introductionmentioning
confidence: 99%
“…The resistance of the rock to the SO 2 ageing test (Table SM5) can be also attributed to its high content of micropores, as pointed out by Ross et al (1989) and Olaru et al (2010). In a comparative study of the ageing test by SO 2 applied to carbonate rocks, the latter authors demonstrated that limestone are more sensible to alteration because of its higher porosity compared to marble, despite they have the same mineralogical and chemical composition.…”
Section: Discussionmentioning
confidence: 78%
“…This is confirmed by the results of. 6,[24][25][26] The erosion effects are not limited to the surface, as acidic pollutants can penetrate into the interior through the pore structure of the stone leading to a further decrease in compressive strength.…”
Section: Variation In the Mechanical Characteristics Of Building Materials (Compressive Strength)mentioning
confidence: 99%